ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI INTELLECTUAL CAPITAL DISCLOSURE DAN PENGARUHNYA TERHADAP COST OF EQUITY CAPITAL (Studi Empiris pada Perusahaan Real Estate dan Properti yang Terdaftar di BEI Tahun 2009-2011) - Maharani Dian Cempaka; Marsono Marsono (Diponegoro Journal of Accounting, 2013)
Intellectual capital becomes an important capital for the company in developing its business. The purposes of this study are to examine the effect of the firm size, leverage, and auditor type on intellectual capital disclosure and examine the effect of intellectual capital disclosure on cost of equity capital. The research used a population of real estate and property listed from BEI. The research used secondary data from annual report of 2009-2011 and IDX Fact book 2010-2012. The analysis method used is multiple linear regression and simple linear regression. The results showed that simultaneously firm size, leverage, and auditor type has significant on intellectual capital disclosure of 30,8%. Individually testing showed firm size has positive effect and significant on intellectual capital disclosure. Leverage and auditor type has no effect on intellectual capital disclosure. Intellectual capital disclosure has a negative effect and significant on cost of equity capital. This proves that large companies tend to have high capital costs can decreased cost of equity capital through increased intellectual capital disclosure.